Pola komunikasi mahasiswa dengan dosen pada kuliah online - Studi Deskriptif Kualitatif Pada Mahasiswa Ilmu Komunikasi Universitas Bengkulu - Paul Julianto Siahaan (UNIVED Press, Universitas Dehasen Bengkulu, 2021)
This study aims to find out how the communication patterns of students with lecturers during lecture activities are carried out online. This study uses the concept of computer mediated communication (CMC) which includes asynchronous communication and synchronous communication. This study uses a qualitative descriptive method by describing how the communication patterns of students and lecturers in online lectures. Determination of informants in this study using purposive sampling technique. Data collection techniques were carried out by interview, observation and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The data validity technique used by the researchers was source triangulation and technical triangulation. The results of this study indicate that communication patterns that occur in online lectures secondary communication pattern tend to be one-way and less interactive. Communication is dominated by lecturers while students do not play an active role in the online lectures, which is caused by environmental factors as well as physical factors such as networks and quotas. Keywords: Communication Pattern, CMC, Online Lecture